"Transformed" Fe3S4 tetragonal nanosheets: a high-efficiency and body-clearable agent for magnetic resonance imaging guided photothermal and chemodynamic synergistic therapy. Issue 37 (18th September 2018) - Guan, Guoqiang; Wang, Xin; Li, Bo; Zhang, Wenlong; Cui, Zhe; Lu, Xinwu; Zou, Rujia; Hu, Junqing
Abstract : The PVP coated Fe3 S4 tetragonal nanosheets could be employed to realize magnetic resonance imaging guided photothermal/chemodynamic therapy and body-clearance without appreciable toxic side effects. Abstract : To retain the agents in tumors for cancer diagnosis and therapy, and then to remove them from the body, are key for the clinical applications of ideal inorganic theranostic agents. To meet these needs, we have developed a transformed theranostic platform, employing PVP coated Fe3 S4 tetragonal nanosheets (TNSs), which could effectively accumulate in the tumor under magnetic targeting, whilst gradually transforming to small particles (∼5 nm) over three weeks. These were then effectively excreted from the body in normal physiological conditions after exerting their therapeutic effect. The aqueous dispersion of PVP coated Fe3 S4 TNSs had an intense near-infrared absorption, excellent photothermal conversion efficiency (64.3%) and great T 2 weighted magnetic resonance imaging properties (71.3 mM −1 S −1 ). In addition, Fe3 S4 TNSs could realize a synergistic photothermal therapy (PTT)/chemodynamic therapy (CDT), because the localized heat produced by PTT from the defect-rich structure could enhance the Fenton process by utilizing the overproduced H2 O2 in the tumor microenvironment, and in return, the produced ˙OH could inhibit tumor growth and recurrence after PPT. We thus developed a high-efficiency inorganic theranostic platform which was effectively cleared from the body. This will open up a new avenue for the design of inorganic agents for clinical applications in the future.